The 'cause' of my cancer, beliefs about cause among breast cancer patients and survivors who do and do not seek IO care. Issue 2 (9th November 2015) - Andersen, M. Robyn; Afdem, Kelsey; Hager, Shelly; Gaul, Marcia; Sweet, Erin; Standish, Leanna J.
Abstract: Objective: We sought to describe survivors' beliefs about the cause of their breast cancer and to test the hypothesis that beliefs about cancer's cause are associated with treatment preferences in accordance with the common sense model of self‐regulation of health and illness. Methods: Breast cancer survivors ( n = 552) participating in an observational study of cancer outcomes responded to an open‐ended question about the cause of their cancer. Of these, 245 women had sought treatment from complementary and alternative integrative oncology (IO) clinics, and 307 women did not. Results: Women frequently described theories for their cancer's cause including genetics and family history (31%), stress and coping (31%), toxins and chemicals (27%), a variety of lifestyle and epidemiological risk factors, and randomness (17%). Self‐reported beliefs about cancer's cause differed among women in association with their use of IO. IO users were somewhat more likely to describe stress and poor coping as causes of their cancer and less likely to describe random chance as a cause of cancer ( p < 0.05). Conclusions: Beliefs about the cause of cancer change over time and may predict decisions to use specific treatment including complementary and alternative medicine and IO. Copyright © 2015 John Wiley & Sons, Ltd.